The Analysis of User Intention to Subscribe Netflix Using UTAUT Framework - M. Saufi; Agus Rofi’i; Dede Ridho Firdaus (Journal of Information System, Technology and Engineering, 2023)
In addition to assessing the degree of satisfaction with the services offered by the streaming application to its customers, this study seeks to identify the elements that motivate streaming application users in Indonesia to renew their subscriptions in the coming months. The research model employed in this study is the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2), which also includes variables for content, ethics, and morality in addition to the variables for the expectation-confirmation model (ECM), specifically satisfaction and intention to continue. This study uses a quantitative method with data analysis using the PLS-SEM method with the help of SmartPLS. According to the study's findings, a number of factors influence how likely users of streaming applications are to renew their subscriptions in the months to come, including content, performance expectations, facilitating conditions, hedonic incentive, price value, habit, morals, and ethics. The findings of this study are anticipated to be taken into account when streaming applications decide whether or not to expand in Indonesia.